Space alternating generalized maximum-likelihood based low-complexity list detection algorithm - Chang-le JING; Xin WANG; Ji-bo WEI; Bin CHEN; Shi-qi WU (Tongxin xuebao)
A space-alternating generalized maximum-likelihood (SAGL) list detection algorithm with lower-complexity for V-BLAST systems was proposed. The sub-detector involved in the proposed list detection algor hm consisted of sim-plified maximum-likelihood (SML) detectors and successive interference cancel ation (SIC) detectors. The proposed al-gorithm could utilize adjacent symbols to realize joint-sliding detection to achieve higher diversity gain, wh le the tradi-tional SIC algorithm was only able to detect a single symbol each time. Moreover, the proposed SAGL algorithm could further iteratively improve the detection results. Ana is and simulation results present the corresponding enhanced per-formance at the cost of slightly increased complexity, compared with the traditional list detection algorithm.